2016
DOI: 10.3998/ark.5550190.p009.562
|View full text |Cite
|
Sign up to set email alerts
|

In situ formed tert-butyl hypoiodite as an efficient oxidant for rapid, room temperature, metal-free aromatization of Biginelli 3,4-dihydropyrimidin-2(1H)-ones under basic conditions

Abstract: A mild, highly efficient synthetic method was developed for the dehydrogenation of 3,4-dihydropyrimidin-2(1H)-ones employing in situ formed tert-butyl hypoiodite under basic conditions. The oxidant was prepared by the reaction of molecular iodine and potassium tertbutoxide. The reaction was carried out in dry tetrahydrofuran at room temperature and high purity products were isolated in high yields after simple work-up. The reaction times (3-10 min.) indicated the new method is superior in comparion to other li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Various ketones possessing α-hydrogen have been alkylated at the α-position in the presence of primary alcohols 74 via a ligand-mediated catalytic dehydrogenation (LMCD) strategy (Scheme 2) and the reactions have been carried out at 120 °C in toluene medium by using the ruthenium( ii ) catalysts 1a – 4a . It has been observed that isolated yield for this reaction is the highest with 3a but in all cases, the yield is quite high.…”
Section: Resultsmentioning
confidence: 99%
“…Various ketones possessing α-hydrogen have been alkylated at the α-position in the presence of primary alcohols 74 via a ligand-mediated catalytic dehydrogenation (LMCD) strategy (Scheme 2) and the reactions have been carried out at 120 °C in toluene medium by using the ruthenium( ii ) catalysts 1a – 4a . It has been observed that isolated yield for this reaction is the highest with 3a but in all cases, the yield is quite high.…”
Section: Resultsmentioning
confidence: 99%